Effect of aluminium toxicity on growth of rice (Oryza sativa) inoculated with N₂ – fixing bacteria - Kang, Yee Farn (2015)
Nitrogen fixing bacteria has high potential to increase rice yield. However, the effects of aluminium (Al) on the population and activities of Stenotrophomonas sp., strain SB16 are still unknown. Laboratory experiments were conducted to determine the effects of aluminium toxicity on population and activity of N2-fixing bacteria on growth of Oryza sativa strain MR220 rice in nutrient solution culture. Four different Al concentrations (0, 15, 30, 45 μM) were used to determine the effect on growth of rice plants in nutrient solution over a period of 30 days. For each level of Al concentrations, 2 different treatments used were with and without N2-fixing bacteria inoculation. The plants were sampled once after 30 days of planting. Experimental design was a factorial complete randomized design (4 Al concentration and 2 inoculation treatments) with 5 replications. All data collected were statistically analyzed using Analysis of Variance (ANOVA) while means of data were compared using Tukey test. The results showed that growth of paddy plants and population of N2 fixing bacteria were affected by increasing concentration of Al. Al made a significant difference in the size of the shoot length in the way that those plants, which were in touch with Al had smaller size compare to the other group. Root volume showed another significant result in which inoculated plants got larger volume compare to non-inoculated ones. Next notable result is plants dry weight. Those rice plants that had contact with Al were extremity lighter than same plants those that had contact with Al. Lastly shoot dry weight is showing an outstanding difference. Weights of the inoculated dry shoots are significantly lighter than non-inoculated plants.